The Progressivity of Islamic Law in the Tradition of Marriage Conditions: An Analysis of the Practice of Planting Durian Trees in Tompo Bulu Village, South Sulawesi - Dian Purnamasari; Norcahyono Norcahyono; Ranti Suminar Endah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the legal progressivity of the obligation to plant durian trees as a condition of marriage, formalized through Village Regulations No. 05/2022 and No. 17/2022 in Tompo Bulu Village, South Sulawesi. In practice, these Village Regulations impose sanctions on prospective brides and grooms who do not comply with the regulation, granting the village imam the authority to refuse to perform a marriage, thus creating direct tension with the pillars and requirements for valid marriage according to the fiqh of munakahat. This study aims to analyze the legitimacy of the Village Regulation's Siyasah Syar'iyyah (Islamic principle), the legal implications of the mechanism for rejecting a marriage contract, and the philosophical values ​​of the tradition of planting durian trees. Using empirical legal research methods and a legal anthropology approach, data were collected through in-depth interviews, field observations, and documentary studies of two relevant Village Regulations. The most important finding of this study is that to date, there has never been a single case of rejection of a marriage contract. 98 percent of village residents voluntarily fulfill the obligation, while the remaining two percent are residents who married outside the village's jurisdiction, making the Village Regulation legally inapplicable to them. This proves that sanctions function as a deterrent mechanism, not as an instrument of punishment.